Interaction of Veratrum nigrum with Panax ginseng against Obesity: A Sang-ban Relationship - Park, Jinbong (Hindawi Publishing Corporation, 2013)
Obesity has become a major health threat in developed countries. However, current medications for obesity are limited because of their adverse effects. Interest in natural products for the treatment of obesity is thus rapidly growing. Korean Medicine (KM) is characterized by the wide use of herbal formulas. However, the combination rule of herbal formulas in KM lacks experimental evidence. According to Shennong's Classic of Materia Medica, the earliest book of herbal medicine, Veratrum nigrum (VN) has antagonistic features against Panax ginseng (PG), and the PG-VN pair is strictly forbidden. In this study, we have shown the effects of PG, VN, and their combination on obesity in high-fat (HF) diet-induced obese mice and in 3T3-L1 cells. PG, VN, and PG-VN combination significantly reduced weight gain and the fat pad weight in HF diet-induced obese mice. They also significantly decreased lipid accumulation and the expressions of two major adipogenesis factors, PPARγ and C/EBPα, in 3T3-L1 cells. In addition, the PG-VN combination had synergistic effects compared with the mixture of extracts of PG and VN on inhibition of PPARγ and C/EBPα expressions at lower doses. These results indicate a new potential anti-obese pharmacotherapy and also provide scientific evidence supporting the usage of herbal combinations instead of mixtures in KM.